Chinese patent medicine combined with calcium channel blockers in the treatment of essential hypertension:a Bayes network meta-analysis and systematic review - Cui, Liangyu; Liu, Xingfang; Li, Yukun; Jing, Tianyue; Liu, Dasheng; Ren, Cong; Yin, Tong; Wang, Yu; Zhao, Zhiwei; Wang, Jiaheng; Han, Xuejie; Wang, Liying (Frontiers in Pharmacology, 2024)
Backgroud: The co-administration of Chinese patent medicine with calcium channel blockers (CCBs) is a prevalent practice in China for treating essential hypertension (EH). However, robust evidence supporting the efficacy and safety of tailored combinations of different Chinese patent medicines with CCBs, according to individual patient conditions, is still limited. This study sought to elucidate the efficacy and safety of these combinations using a systematic review and network meta-analysis. Materials and methods: Relevant studies were sourced from established databases, incorporating randomized controlled trials published up to 1 February 2023. The ROB2 tool from the Cochrane Collaborative Network was employed to independently assess and cross-verify the quality of the included literature. A network meta-analysis was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) 2020 and PRISMA-Network Meta-Analyses (PRISMA-NMA) guidelines. A Bayesian network meta-analysis was utilized to gauge the efficacy and safety of distinct integrations of Chinese patent medicine and CCBs. Primary outcomes were interpreted using a paired fixed-effect meta-analysis. Publication bias was appraised through Egger’s test and represented with funnel plots. All statistical analyses were executed within the R statistical framework. Results: Following rigorous selection, data extraction, and bias evaluation, 36 articles were incorporated. Tianma Gouteng Granule, when combined with CCBs, displayed superior efficacy in reducing systolic blood pressure (SBP). In terms of diastolic blood pressure (DBP) reduction, Songling Xuemaikang Capsule combined with CCBs emerged as the most effective. Regarding enhancement of antihypertensive effective rates, Qinggan Jiangya Capsule paired with CCBs demonstrated optimal results. For diminishing Traditional Chinese Medicine syndrome scores, the Qiangli Dingxuan Tablet and CCBs combination proved most beneficial. When aiming to reduce total cholesterol (TC), triglycerides (TG), and low-density lipoprotein cholesterol (LDL-C) levels, Tianma Gouteng Granule and CCBs showcased superior results. In contrast, the combination of Songling Xuemaikang Capsule and CCBs was more effective in reducing LDL-C, tumor necrosis factor-alpha (TNF-α), and interleukin-6 (IL-6). Conclusion: This study underscores variability in outcomes from combining Chinese patent medicine and CCBs for hypertension, emphasizing the importance of personalized medicinal combinations, especially Tianma Gouteng Granule and Songling Xuemaikang Capsule. The results offer robust evidence to inform clinical guidelines for essential hypertention and significantly aid clinician in seleting appropriate Chinese patent medicines for treatment.